Topical EMLA Cream as a Pretreatment for Facial Lacerations - Park, Sung Woo; Oh, Tae Suk; Choi, Jong Woo; Eom, Jin Sup; Hong, Joon Pio; Koh, Kyung S; Lee, Taik Jong; Kim, Eun Key (Archives of Plastic Surgery, 2015)
Background Topical anesthetics, such as eutectic mixture of local anesthetics (EMLA) cream, can be applied to reduce pain before minor procedure. This trial evaluated EMLA as pretreatment for facial lacerations and compared pain, discomfort and overall satisfaction.Methods This trial included consecutive emergency department patients ≥16 years of age who presented with simple facial lacerations. At triage, lacerations were allotted to either the routine processing group or EMLA pretreatment group according to date of admission. Initially, the emergency department doctors inspected each laceration, which were dressed with saline-soaked gauze. In the pretreatment group, EMLA cream was applied during wound inspection. The plastic surgeon then completed primary closure following the local injection of an anesthetic. After the procedure, all patients were given a questionnaire assessing pain using the 10-point visual analog scale (VAS) ("no pain" to "worst pain"). All questionnaires were collected by the emergency department nurse before discharge.Results Fifty patients were included in the routine processing group, and fifty patients were included in the EMLA pretreatment group. Median age was 39.9 years, 66% were male, and the average laceration was 2.67 cm in length. The EMLA pretreatment group reported lower pain scores in comparison with the routine processing group (2.4 vs. 4.5 on VAS, P<0.05), and lower discomfort scores during the procedure (2.0 vs. 3.3, P=0.60). Overall satisfaction was significantly higher in the EMLA pretreatment group (7.8 vs. 6.1, P<0.05).Conclusions Pretreating facial lacerations with EMLA topical cream aids patients by reducing pain and further enhancing overall satisfaction during laceration treatment.
Keywords: EMLA; Lacerations; Anesthetics, local